Parental Socialization Styles: The Contribution of Paternal and Maternal Affect/Communication and Strictness to Family Socialization Style - Axpe, Inge (Int J Environ Res Public Health, 2019)
The aim of this study is two-fold: (a) to determine the general degree of family affect/communication and strictness by examining the combination of the two classical dimensions of mother parenting style: affect/communication and strictness, and (b) to analyze the impact of both parents’ affect and strictness on the family style, thereby exploring the specific contribution made by each parent’s style and dimension. Participants were 1190 Spanish students, 47.1% boys and 52.3% girls (M = 14.68; SD = 1.76). The Affect Scale (EA-H) and the Rules and Demandingness Scale (ENE-H) (both by Fuentes, Motrico, and Bersabé, 1999) were used. Structural equation models (SEMs) were extracted using the EQS program. The results reveal that it is not the father’s and the mother’s parenting style combined, but rather the combination of maternal and paternal affect/communication, and maternal and paternal strictness which generates one perception of family affect and another of family strictness. The results also indicated that the weight of both dimensions varies in accordance with the parent’s gender, with maternal dimensions playing a more important role in family socialization style.